USING FACEBOOK MOVIE CLUB TO DEVELOP 21ST CENTURY SKILLS - Olena Zmiyevska; Tamara Glazunova (Pavlo Tychyna Uman State Pedagogical University, 2018)
The article deals with the experience of using Facebook discussion group as a platform for the development of 21st century life skills, such as critical thinking, communicative, social and computer skills with University students. The choice of Facebook group as a learning tool is explained by its user-friendliness, multi-functional character and growing popularity with young people.  The procedure of administering and monitoring Facebook Movie Club discussion is described. After getting registered in the closed discussion group, the students are supposed to upload their initial post, read and comment on at least two other posts, respond to the comments of instructors and group mates or start a new discussion thread. They are also introduced to the conditions of the discussion - to be open and friendly, polite and tolerant of other participants' opinions. Assessment criteria are provided in the Grading Rubric. The advantages of using Facebook discussion are specified, among which are its student-centeredness, real life character of learning and motivational potential. Problems arising in the process of the discussion are connected with the necessity of constant monitoring on the part of the instructors in order to exclude inappropriate content and to keep the track of the discussion. Qualitative analysis of the students' feedback proves positive results and effectiveness of the discussion.